Does money growth predict inflation? Evidence from vector autoregressions using four centuries of data - Rodney Edvinsson; Sune Karlsson; Pär Österholm (Örebro University School of Business, 2023)
In this paper, we add new evidence to a long-debated macroeconomic question, namely whether money growth has predictive power for inflation or, put differently, whether money growth Granger causes inflation. We use a historical dataset - consisting of annual Swedish data on money growth and inflation ranging from 1620 to 2021 - and employ state-of-the-art Bayesian estimation methods. Specifically, we employ VAR models with drifting parameters and stochastic volatility which are used to conduct analysis both within- and outof-sample. Our results indicate that the within-sample analysis - based on marginal likelihoods - provides strong evidence in favour of money growth Granger causing inflation. This strong evidence is, however, not reflected in our out-of-sample analysis, as it does not translate into a corresponding improvement in forecast accuracy.
Keywords: E31; E37; E47; E51; N13; 330; Time-varying parameters; Stochastic volatility; Out-of-sample forecasts